Пещера - Роллинс Джеймс (Книга-загадка, книга-бестселлер, 2008)
Экземпляры: ф13 (20191112) / Инвентарный номер: 58441 / Цена: 250.00 / Сис.шифр: И(англ) / Авт.знак: Р 67 / ГРНТИ: 17.82.30 / ББК: 84(7Сое)